Learning in a Family Business Through Intermarriage: A Rhetorical History Perspective. (March 2023) - McAdam, Maura; Clinton, Eric; Hamilton, Eleanor; Gartner, William B.
We use concepts from rhetorical history and mnemonic communities to expand on the notion of "intermarriage" in a family business as the merger of shared histories among family members, nonfamily members, and individuals from other families and suggest that a common mnemonic narrative defines the parameters of the family business rather than the structural properties of the firm or the genetic relationships among family members. Our analysis reveals how fundamental family business practices can be changed when confronted with the intimate knowledge of the rhetorical history of the failure of others.